A systems perspective on systemic innovation. (7th November 2021) - Midgley, Gerald; Lindhult, Erik
Abstract: The term 'systemic innovation' is increasing in use, but there is no consensus on its meaning: five understandings of the term can be identified, each based on a different view of what the word 'systemic' should refer to. The first understanding focuses on technologies, where the innovation in focus is synergistically integrated with other complementary innovations, going beyond the boundaries of a single organization. Therefore, 'systemic' refers to technological innovations interacting in a larger product system. A second use of the term refers to the development of policies and governance at a local, regional or national scale to create an enabling environment for innovation systems. Here, 'systemic' means recognition that innovation systems can be enabled and/or constrained by a meta‐level policy system. The third use of the term says that an innovation is 'systemic' when its purpose is to change societal laws and norms to place new enablers and constraints on innovation in the interests of ecological sustainability. What makes this systemic is acknowledgement of the existence of nested systems: innovation systems are parts of economic systems, which are parts of societal systems, and all societies exist on a single planetary ecosystem. The fourth use focuses on collaboration in innovation networks with multiple actors. This has evolved from the first understanding of systemic innovation, but the critical difference is the primary focus on people and processes rather than technological products. The word 'systemic' refers to the interdependency of actors in a business or community context, leading to a need to cocreate value and innovate in concert or through coevolutionary dynamics. The fifth use of the term 'systemic innovation' concerns how people engage in a process to support systemic thinking and action, and it is primarily this process, and the thinking and action it gives rise to, that is seen as systemic, rather than the innovation system that they exist within or are trying to create. It is this fifth understanding that accords with most of the literature on systems thinking published over the last 50 years. The current paper offers a contemporary perspective on what systems thinkers mean by 'systemic', and this not only enables us to provide a redefinition of 'systemic innovation', but it also helps to show how all four previous forms of innovation that have been described as systemic can be enhanced by the practice of systems thinking.